Analisis Penerapan E-System Perpajakan Pada Wajib Pajak Pribadi Terhadap Pelaksanaan Self-Assessment System Dalam Memenuhi Kewajiban Perpajakan - Helen Widjaja; Arthur Jaya Siagian (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
E-system Modernization taxation is using information technology to the system is expected to facilitate taxpayers to report tax. The use of advanced electronic information in Taxation is expected to improve service to the taxpayer, both in terms of quality and time to be more effective. The objective is to determine the effectiveness of the use of the e-taxation systems in the form of e-registration,e-SPT, e-filing, e-billing affect the fulfilment of tax obligations, personal taxpayers. The research method used in this study is a research approach Explorative. This research was conducted through interviews, observation, and documentation on KPP Pratama Kebayoran Baru Tiga South Jakarta. The results of this study indicate that the e-system on KPP Pratama Kebayoran Baru Tiga effectively and efficiently.